Toxicity Assessment Of Glycofurol In Zebrafish And In Silico Admet Profiling - P. Arun; P. Jalantha; C. Soundararajan; M. R. Srinivasan (The Indian Veterinary Journal, 2024)
This study assessed glycofurol's embryo and adult toxicity in zebrafish, a solvent widely used in pharmaceuticals. Despite its common use, limited toxicity data exists in rodents, prompting the examination of acute toxicity in adult zebrafish and developmental toxicity in embryos. Following OECD guidelines 236 and 203, Fish Embryo Acute Toxicity (FET) and Fish Acute Toxicity Testing were conducted. Results showed concentration-dependent embryo mortality with LC50 based on the Probit method of analysis is 0.36%. The adverse effects in embryos like coagulation, lack of somite formation and various such changes were observed at 0.4% and above. Adult zebrafish exhibited no mortality or abnormal signs at the 0.2 ml/L concentration of glycofurol. Based on the results obtained, glycofurol is safe at concentration of 0.2% in zebrafish FET and 0.2 ml/L in adult zebrafish acute toxicity test. In silico prediction of pharmacokinetics and toxicity profiles showed that the glycofurol has favourable PK (pharmacokinetics) properties and no serious toxicities were predicted.